Orchestrating (bio-)diversity: the secretariat of the convention of biological diversity as an attention-seeking bureaucracy - Jörgens, H.; Kolleck, N.; Saerbeck, B.; Well, M. (International bureaucracy: challenges and lessons for public administration research, 2017)
Conceptualizing international public administrations (IPAs) as attention-seeking bureaucracies which aim to actively feed their policy-relevant information into multilateral decision-making process, the chapter proposes two pathways through which international treaty secretariats may seek to influence international negotiations: (a) secretariats may attempt to supply policy-relevant information to negotiators from the inside via their close cooperation with the chairs of multilateral negotiations; (b) they may attempt to build support for their preferred policy outputs by engaging with and communicatively connecting actors within the broader transnational policy network in order to exert pressure on negotiators from the outside. Taking the secretariat of the Convention of Biological Diversity (CBD) as an example, these potential pathways of secretariat influence are illustrated and explored empirically. The findings contribute to a growing body of literature that studies the role of national and IPAs as agenda-setters, policy entrepreneurs, or policy brokers at the interface of public policy analysis and PA.